The effect of applying inquiry-based practicum method toward science process skills on topic related to pollen characteristics and embryogenesis stages of Capsella sp. - Hardini Puspitaningrum; Eni Nuraeni (BIO-INOVED : Jurnal Biologi-Inovasi Pendidikan, 2024)
Science process skills can be improved through direct experience in an inquiry-based practicum. In general, science process skills can include some activities, like observing, comparing, predicting, classifying, measuring, using tools, communicating, and interpreting data. This study aims to determine the effect of implementing a structured inquiry-based practicum on the pollen characteristics and embryogenesis stages of Capsella sp. in improving science process skills possessed by students. The samples in this study were students who took the plant development course, for a total of 31 people. This type of research is qualitative and descriptive. The data collection technique uses a questionnaire in the form of a response questionnaire and student opinion toward the implementation of the practicum, as well as the results of the practicum reports. The results showed that the students' science process skills belonged to the Very High category based on the questionnaire data, and the completeness level reached about 100% in the evaluation of practicum reports with a class average value of 85.86 in six indicators. Based on the results of the questionnaire data and practicum reports, it was concluded that the structured inquiry-based practicum activity in the plant development course can affect students' science process skills positively.Abstrak. Keterampilan proses sains pada peserta didik dapat ditingkatkan melalui pengalaman langsung dalam kegiatan praktikum yang berbasis inkuiri. Keterampilan proses sains secara umum dapat meliputi aktivitas, seperti observasi, membandingkan, memprediksi, mengklasifikasikan, mengukur, menggunakan alat, mengomunikasikan serta menginterpretasi data. Penelitian ini bertujuan untuk mengetahui pengaruh dari pelaksanaan praktikum berbasis structured inquiry pada materi karakteristik polen dan tahapan embriogenesis dari Capsella sp. dalam meningkatkan keterampilan proses sains yang dimiliki oleh praktikan. Sampel dalam penelitian ini adalah mahasiswa yang mengambil mata kuliah perkembangan tumbuhan dengan total sebanyak 31 orang. Jenis penelitian ini adalah penelitian deskriptif kualitatif. Teknik pengumpulan data dilakukan dengan menggunakan kuesioner berupa angket respon dan tanggapan mahasiswa terhadap pelaksanaan praktikum, serta hasil laporan praktikum. Hasil penelitian menunjukkan bahwa keterampilan proses sains praktikan secara keseluruhan tergolong dalam kategori Sangat Tinggi berdasarkan data kuesioner, serta tingkat ketuntasan mencapai 100% pada penilaian laporan hasil praktikum dengan nilai rata-rata kelas mencapai 85,86 pada enam indikator. Berdasarkan hasil data kuesioner dan laporan praktikum, dapat disimpulkan bahwa kegiatan praktikum berbasis structured inquiry pada mata kuliah perkembangan tumbuhan dapat memberikan pengaruh positif terhadap keterampilan proses sains dari peserta didik.